MENGAWAL KESEHATAN KELUARGA MELALUI PEMILIHAN DAN PENGOLAHAN PANGAN YANG TEPAT - Siahaan, Riana Frisca (Universitas Negeri Medan, 2017)
Every day humans would need to eat. How many human activities concerned with eating said, would be a very long list. But from the dining events will be the question. Is it a healthy food? And even a healthy diet? Of course the answer will vary. Depending on the level of nutrition knowledge and awareness of the person. For that it is important knowledge of nutrition, so that can be applied in everyday life. Especially for women. Why? Because usually, the women who have the opportunity and the ability to better manage their family consumption. Although it is possible, men also have the ability in this regard. For women, it would certainly be an honor in itself. Due to the provision of healthy food in the family, God willing, the condition of every member of the family would be more secure. With good body condition, it will be able to support them in order to excel. Thus, the role of women is important to support the success of each member of the family.